2008
DOI: 10.1074/jbc.m709176200
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ionization Mass Spectrometry and Exogenous Heavy Isotope-labeled Lipid Species Provide Detailed Information on Aminophospholipid Acyl Chain Remodeling

Abstract: Mammalian cells maintain the phospholipid compositions of their different membranes remarkably constant. Beside de novo synthesis, degradation, and intracellular trafficking, acyl chain remodeling plays an important role in phospholipid homeostasis. However, many key details of this process remain unresolved, largely because of limitations of existing methodologies. Here we describe a novel approach that allows one to study metabolism of individual phospholipid species in unprecedented detail. Forty different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 75 publications
4
48
0
Order By: Relevance
“…It is tempting to speculate that substrate efflux propensity could be a critical factor regulating homeostatic phospholipases as well. Supporting this suggestion, exogenous phospholipids with short/less hydrophobic chains were rapidly hydrolyzed in cultured cells (20). The high throughput approach used here provides a powerful tool to study the factors underlying the specificity of homeostatic PLA 2 s, because it allows one to determine the rates of hydrolysis of multiple molecular species in very complex mixtures as found in biological membranes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is tempting to speculate that substrate efflux propensity could be a critical factor regulating homeostatic phospholipases as well. Supporting this suggestion, exogenous phospholipids with short/less hydrophobic chains were rapidly hydrolyzed in cultured cells (20). The high throughput approach used here provides a powerful tool to study the factors underlying the specificity of homeostatic PLA 2 s, because it allows one to determine the rates of hydrolysis of multiple molecular species in very complex mixtures as found in biological membranes.…”
Section: Discussionmentioning
confidence: 91%
“…However, it is not clear how those PLAs are regulated (e.g. how they can effectively hydrolyze particular phospholipid species while leaving similar ones intact) (20). It is tempting to speculate that substrate efflux propensity could be a critical factor regulating homeostatic phospholipases as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that certain cyclodextrins can be used to transfer hydrophobic lipids to cells ( 5,10,11 ), but the parameters affecting transfer effi ciency and the possible deleterious effects on cells have not been systematically studied. In the present study, we studied these issues in detail and the key result was that with most phospholipids the amount transferred to cells increased systematically with increasing i ) donor vesicle concentration, ii ) time, and iii ) me ␤ -CD concentration.…”
Section: Effects On Cell Growth and Viabilitymentioning
confidence: 99%
“…Baby hamster kidney (BHK21) and HeLa cells were grown as previously ( 5,18 ). Human skin fi broblasts were grown in RPMI medium containing 15% FBS, 200 U/ml penicillin, 200 µg/ml streptomycin, 2 mM L-glutamine, and 0.1 mM unessential amino acids.…”
Section: Cell Culturementioning
confidence: 99%